When pain really matters: A vicarious-pain brain marker tracks empathy for pain in the romantic partner. (August 2020) - López-Solà, Marina; Koban, Leonie; Krishnan, Anjali; Wager, Tor D.
Abstract: In a previous study (Krishnan, 2016) we identified a whole-brain pattern, the Vicarious Pain Signature (VPS), which predicts vicarious pain when participants observe pictures of strangers in pain. Here, we test its generalization to observation of pain in a close significant other. Participants experienced painful heat (Self-Pain) and observed their romantic partner in pain (Partner-Pain). We measured whether (i) the VPS would respond selectively to Partner-Pain and (ii) the Neurologic Pain Signature (NPS), a measure validated to track somatic pain, would selectively respond to Self-Pain, despite the high interpersonal closeness between partners. The Partner-Pain condition activated the VPS (t = 4.71, p = 0.00005), but not the NPS (t = −1.03, p = 0.308). The Self-Pain condition activated the NPS (t = 13.70, p < .00005), but not the VPS (t = −1.03 p = 0.308). Relative VPS-NPS response differences strongly discriminated Partner-Pain vs. Self-Pain (cross-validated accuracy=97%, p < .000001). Greater interpersonal closeness between partners predicted greater VPS responses during Partner-Pain (r = 0.388, p = 0.050) and greater unpleasantness when observing the romantic partner in pain (r = 0.559, p = 0.003). The VPS generalizes across empathy paradigms and to an interactive social setting, and strongly activates when observing a close significant other in pain. VPS responses may be modulated by relevant interpersonal relationship factors. Self-Pain and Partner-Pain evoke non-overlapping large-scale neural representations. Highlights: A vicarious-pain brain marker (VPS) tracks empathy for pain in the romantic partner. The VPS generalizes to an ecologically valid model of interpersonal empathy. Non-overlapping whole-brain representations between Self-Pain and vicarious pain. VPS responses during Partner-Pain predicted interpersonal closeness.